The Courage of the Consciousness. The French Reception of Edith Stein - Przybylska, Nelli (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2016)
In the 1930s, Edith Steinattends a phenomenological conference in Juvisy (where she meets Jacques Maritain), therebyentering the French intellectual world. Stein knows French: she is interested in the Carmel in France, including the Carmelites of Compiegne, whom remind her of the death of expiatory sacrifice. And yet the position of Stein and her ideas in the French humanistics is problematic. The current principle of secularism certainly constitutes a resistance to the adoption of Stein’s works in France. Moreover, for a long time Stein’s works were neither translated nor published and as consequence the French philosophical world for years could not read and confront her thoughts. The reception of her works has been recently changing. Perhaps Stein, being a Jew and a German woman, aids a multireligious, multicultural and secularised society.